(untitled) (Forum for Linguistic Studies, 2024)
Web programming is an extremely important key skill for students in the information technology field, and effective teaching methods are essential to ensure in-depth understanding and optimal use. This study investigates the effectiveness of using web learning media in teaching web programming at the undergraduate level. This research involved student participants from several information technology study programs at universities. Participants will be divided into two groups, namely the experimental group which will receive web programming instruction using interactive web learning media, and the control group which will receive conventional instruction using textbooks and lectures. Data will be collected through initial tests before teaching begins, final tests after teaching is completed, as well as questionnaires and interviews to collect responses and experiences from participants regarding the use of web learning media. The results of the two groups will be analyzed comparatively to measure the level of understanding of web programming concepts, practical skills, and the level of student engagement and satisfaction. This research shows that teaching web programming using web learning media can significantly improve students’ understanding and skills compared to conventional teaching methods. This research provides valuable insights for curriculum development and teaching strategies at the undergraduate level in the field of information technology, as well as providing a foundation for the use of web learning media in higher education contexts.